PERSEPSI KONSUMEN TERHADAP MARKETPLACE TOKOPEDIA DAN SHOPEE DI KECAMATAN CIBINONG KABUPATEN BOGOR - Adyas, Dasmansyah; Nur Cahyani, Desy (Economicus, 2020)
This study aims to determine how consumers perceive the Tokopedia and Shopee marketplaces on the dimensions of product, price, promotion, and ease of use, namely in the community in the Cibinong District, Bogor Regency. This research uses descriptive research with a quantitative approach and uses data analysis techniques Weighted Means Score (WMS) by comparing the average value of each variable. Analysis of the assessment of consumer perceptions of the Tokopedia and Shopee markets is measured by a Likert scale using a questionnaire distributed to 150 respondents who have purchased at the Tokopedia and Shopee markets. The results of this study indicate that the product variable (X1) Shopee (with a score of 4.35) is superior to Tokopedia (with a score of 4.01), on the price variable (X2) Shopee (with a score of 4.24) is superior to Tokopedia ( with a score of 3.98), on the promotional variable (X3) Shopee (with a score of 4.38) was superior to Tokopedia (with a score of 4.07), and on the variable using Shopee (X4) (with a score of 4.42) was more superior to Tokopedia (with a score of 4.21).